Kekuatan Keterangan Saksi Sebagai Alat Bukti Pada Perkara Kekerasan Dalam Rumah Tangga - Elias Zadrack Leasa (Criminal of Law Department, Faculty of Law, Pattimura University, 2019)
A witness is someone who hears, sees and experiences on something that happens. This witness has an important role in disclosing a problem that occurs including legal issues. The description of this witness is very useful for the sake of investigation, prosecution and justice on a matter heard by the witness himself, witness to see himself and his own natural witness. The information of a witness alone is not sufficient to prove a criminal incident in accordance with the principle of Unus Testis Nulus Testis (Article 185 paragraph (2) KUHAP), then the statements of witnesses having blood relation under Article 168 Criminal Procedure Code can not be accepted as valid evidence . Witnesses in domestic violence are very difficult because the cases that occur within the household are very small and the witness has a blood relation, but in abolition of domestic violance act in Article 55 provides an opportunity if only one witness is provided with another legal evidence, concerning the witness who incest abolition of domestic violence act is a lex specialist from KUHAP.